Newsweek discourses on China and their Korean translations: A corpus-based approach. (March 2017) - Kim, Kyung Hye
Abstract: Employing a corpus-based methodology and drawing on critical discourse analysis, this study examines news stories about China published in Newsweek and the Korean translations of these stories in Newsweek Hangukpan, the Korean-language version of Newsweek . In so doing, it aims to identify the manner in which China is constructed in the articles selected to be translated for Newsweek Hangukpan and to examine any discursive shifts in the Korean translations. The corpus for this study consists of two separate sub-corpora, designed and compiled using the same criteria and specifications: one sub-corpus consists of English-language texts published in Newsweek from 2005 to 2015, and the other sub-corpus consists of their corresponding Korean-language translations published in Newsweek Hangukpan during the same period. Since news texts produced outstrip the translations, the selection process is largely inevitable and only certain texts are selected for translation; and the socio-political principles or slants of particular news outlets affect which texts are so selected. In this context, the analysis reveals that Newsweek Hangukpan emphasises issues that are directly related to South Korea by prioritising, translating, and highlighting these materials, among other news available for translation; simultaneously, it distances itself from certain views advanced in the English source text by reconstructing the voice from its own perspective and using subtle linguistic changes whenever an argument cannot be applied to the South Korean context, such as by downgrading the marked voices in the Korean translations.